Pembangunan dan pelaksanaan demokrasi di Malaysia dan Indonesia: Suatu perbandingan - Eby Hara, Abubakar; Omar, Rusdi (2011)
This paper attempts to compare development and implementation of liberal democracy in Indonesia and Malaysia. Using standards in democracy such as the level of freedom and equality, Indonesia may have more freedom and equality than that in Malaysia.However, this paper argues, the development of democracy cannot be measured only from the level of freedom and equality. It should be examined from how elite and people in those countries understand, debate and adapt democracy to their local needs and contexts.Localization process can give more respect, justice and dignity to people in these two countries. Seeing from this localization process. We will have mixed results of implementation of democracy. In Indonesia, the adoption of democracy has created problems of social order and security. Neither does it make people participation in controlling the government effective. In Malaysia,democracy implemented has been adjusted to suit its multicultural society by limiting certain rights and freedom to speech. The result is that we can see a relatively more stable and responsive political system in Malaysia than that in Indonesia. Given this condition, these two countries have to cope with two different challenges. Indonesia faces growing demands for stability, order, fairness and responsiveness of the government while Malaysia faces growing demands for more freedom and equality in their society. The future of democracy in these two counties relies very much on how the two countries are able to handle these challenges.